La représentation de la douleur dans la sculpture hellénistique - François Queyrel (Pallas, 2012)
It is often thought that the representation of physical pain flourished in Hellenistic sculpture, with the whole “pathetic” trend often associated with the Pergamene school. The spectator’s perception of physical pain is first linked to the staging, which may be confusing. Such is the case of the “Dying Seneca” – a statue restored in the xvith c. ; the philosopher is supposed to be cutting his veins, whereas it is actually the statue of an old, prematurely worn-up fisherman, but who was not perceived as suffering by spectators from the Antiquity. However, the invention of conventional expressions of pain dates back to classical art with centaur figures grimacing on Parthenon’s metopes. Such grimaces are not to be seen on the Galates’faces in the « great Attalid ex-voto » : the physical pain that is expected does not show at all. Such an indifference to pain gives an inhuman side to the Barbarian figure. The study of Marsyas’and Laocoon’s expression also leads to the ironic conclusion that the expression of physical pain resides more in the staging than in the expression of pain felt by the character.